Climate change and antimicrobial resistance: a global public health crisis at the environmental nexus - Purwaningrum, Dyah; Pratama, Alvin (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2024)
Antimicrobial resistance (AMR) and climate change are major global public health challenges, with growing evidence indicating interconnected relationships. This review explores the multifaceted links between climate change and AMR, focusing on how rising temperatures influence bacterial resistance mechanisms, alter pathogen distribution patterns, and affect environmental reservoirs of resistance genes. Evidence synthesized in this review indicates that rising temperatures correlate with increased AMR rates across multiple regions, with each 1°C temperature increase linked to higher resistance prevalence. Climate change affects environmental transmission dynamics via soil ecosystems, aquatic environments, and cryosphere degradation, which can release long-dormant resistance determinants from permafrost and glaciers. Rising temperatures facilitate the geographic spread of resistant pathogens, as observed in Vibrio species expanding to higher latitudes and the emergence of Candida auris as a clinically significant pathogen from environmental sources. Wildlife and livestock act as potential reservoirs, while climate-driven habitat changes increase human-animal interactions that may facilitate transmission. The bidirectional relationship between these challenges—where rising temperatures contribute to AMR spread and resistant infections may hinder climate resilience—requires integrated One Health approaches. Strategies proposed include enhanced surveillance, climate-informed antimicrobial stewardship, and ecosystem-based interventions to address these interconnected issues. Importantly, integrating climate-informed health policies that align climate adaptation with AMR control should be prioritized globally to safeguard antimicrobial efficacy amid accelerating environmental changes.